APPLICATION OF A SCIENTIFIC APPROACH AND MEDIA MODIFICATION IN IMPROVING CHEST PASS LEARNING OUTCOMES BASKETBALL - Simbolon, Leonardo Efan (Universitas Negeri Medan, 2024)
This research aims to determine the improvement in learning to play the chest pass in the game of basketball through the application of a scientific approach and modified plastic ball media in class VIII students at Santa Lusia Sei Rotan Middle School in the 2016 academic year. The student's ability to perform chest passes is still low. This research uses the Classroom Action Research method which consists of two cycles. The subjects in this research were 30 class VIII junior high school students. The results of cycle research showed that 16 people (53.33%) completed the chest pass study and 14 people (46.67%) did not complete it. Student learning outcomes in doing chest passes in cycle I were average (69.2%). In cycle II, it showed that the results of the complete chest pass study were 26 people (86.67%), and 4 people (13.33%) did not complete it. Student learning outcomes in cycle II were average (80.0%). This research concludes that the application of a scientific approach has a significant influence on chest pass learning outcomes.